Editor’s Introduction: Arts and Community Engagement: Intersect Music, Dance and Drama in Arts Education, Arts Therapy, and Arts Practice with Community Engagement Projects - Hanafi Hussin, (Wacana Seni Journal of Arts Discourse, 2024)
This special edition is an eclectic collection of writings focusing on Arts and Community Engagement. The articles differ from academic research and research by practice to first voice account of engagement in different communities in Malaysia, exploring voices and positioning of different stakeholders, including marginalised community members, academics, and art practitioners. This issue acknowledges different approaches and experiences to community engagements, mostly within academia, yet with a strong critical approach and a desire to raise awareness of what is possible and provide good models for future engagements. Two articles focus on therapeutic intervention through arts (dance and music); the first examines the benefits of dance and music for breast cancer survivors, and the other highlights how music therapy enhances the cognitive function and quality of life of seniors with dementia and focuses on breast cancer survivors, and the other focuses on seniors with dementia. Another article explores the challenges and prospects of music therapists. One of the articles investigates the making of the wheelchair dance using disabled dancers. Three articles address the different facets of arts for children. One of the articles focused on teaching music through a flipped classroom, an alternative online method.